Food Credence Attributes: A Conceptual Framework of Supply Chain Stakeholders, Their Motives, and Mechanisms to Address Information Asymmetry - Peggy Schrobback; Airong Zhang; Barton Loechel; Katie Ricketts; Aaron Ingham (Foods, 2023)
Food credence attributes (e.g., food safety, organic, and carbon neutral production methods) are quality characteristics of products that cannot be assessed by buyers at the point of sale without additional information (e.g., certification labels). Hence, the ability to access credence attributes of a particular product can result in a situation termed as asymmetric distributed information among supply chain stakeholders (e.g., producers, processors, wholesalers, retailers, consumer) where one party of a market transaction is in possession of more information about a product than the other party. This situation can lead to potential inefficiencies, e.g., misinformation, risk of food borne illness, or opportunistic behavior such as fraud. The present study sought to develop a conceptual framework that describes a) the motivation for key stakeholders to participate in the market for food credence attributes, b) the type of food credence attributes that key stakeholders provide, and c) current mechanisms to address the issue of information asymmetry among the stakeholders in the food system. The study was conducted using an integrative literature review. The developed framework consists of two components: a) the food supply chain and b) the attribute assurance system among which multiple links exist. The findings suggest that retailers, processors, NGOs, and government authorities are influential stakeholders within the supply chain of food credence attributes by imposing food quality standards which can address information asymmetry among food actors. While the credence attribute assurance system (e.g., food standards, third party food attribute assurance providers) can potentially address the issue of asymmetric information among market stakeholders, a range of issues remain. These include food standards as a potential market entry barrier for food producers and distributors, limited food standard harmonization, and communication challenges of food attribute assurance (e.g., consumers’ signal processing, signal use and trust). The syntheses presented in this study contributes to stakeholders’ (e.g., supply chain actors, scientists, policy makers) improved understanding about the components of the credence food system and their integration as well as the drivers for change in this system.